The Effect of Financial Literation and Financial Attitude on Financial Behavior in Modernization Era (Case study on employees of PT. Paluta Inti Sawit) - Shelvina; Nainggolan, Susan Grace V. (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
ABSTRACT This study aims to determine whether financial literacy and financial attitude have a significant effect on financial behavior in modernization era among employees of PT. Paluta Inti Sawit. The study uses quantitative data method and the data source is primary data. The population in this study are all employees with top and middle management levels working at PT. Paluta Inti Sawit, totaling 38 employees. The sample in this study includes all employees at the top and middle management levels working at PT. Paluta Inti Sawit, using a saturated sampling method. Data analysis and testing consist of validity test, reliability test, descriptive statistics, the classical assumption test, multiple regression analysis, partial hypothesis testing (T test) and simultaneous hypothesis testing (F test), and coefficient of determination test (R²). The results of this study show that financial literacy has a significant effect on financial behavior, with a calculated T-count of 3.182 > T-table of 2.028. Financial attitude also has a significant effect on financial behavior, with a calculated T-count of 3.925 > T-table of 2.028. Financial literacy and financial attitude have a significant effect on financial behavior, with a calculated F-count of 22.077 > F-table of 3.27 and the regression coefficient is 55,8%. Keywords: Financial Literacy; Financial Attitude; Financial Behavior